2008
DOI: 10.1007/s10620-008-0539-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Visfatin on Histopathological Changes of Non-alcoholic Fatty Liver Disease

Abstract: The mean age was 42.8 +/- 11.2 years, the mean BMI was 33.1 +/- 10.2 with 37 males (67.3%) and 18 females (32.7%). Probabilities to have; portal inflammation increased 1.11 (CI95%:1.03-1.50) with each increment of 1 ng/ml of visfatin concentration, high grade of steatosis increased 1.25 (CI 95%:1.06-1.61) with each unit of insulin concentrations, fibrosis increased 1.12 (CI 95%:1.02-1.43) with each unit of fat mass and lobulillar inflammation increased 13.4 (CI 95%:1.3-147) with each unit of HOMA-IR. Portal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
2
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 18 publications
3
64
2
8
Order By: Relevance
“…Some reports have suggested that both tissue and circulating visfatin levels are increased in inflammatory disorders [9][10][11]. It has been shown that FFAs play a significant role in hepatic inflammation and insulin resistance [4] and that the liver secretes visfatin [6,7]. Thus, it was hypothesized that visfatin is associated with hepatic inflammation in an insulin-resistant state with high FFA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have suggested that both tissue and circulating visfatin levels are increased in inflammatory disorders [9][10][11]. It has been shown that FFAs play a significant role in hepatic inflammation and insulin resistance [4] and that the liver secretes visfatin [6,7]. Thus, it was hypothesized that visfatin is associated with hepatic inflammation in an insulin-resistant state with high FFA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin was recently identified as an adipocytokine preferentially expressed in visceral adipose tissue [5]. It is also present in skeletal muscle, bone marrow, hepatocytes, and lymphocytes, where it was initially identified as pre-Bcell colony-enhancing factor [6,7]. Visfatin has been described as a highly expressed protein with insulin-mimetic biological and physiological effects [5]; however, these properties have not been confirmed using in vivo and in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated concentrations of hepatic enzymes exhibited by the obese patients may be influencing NAMPT concentrations or, conversely, NAMPT may be exerting an effect on the concentrations of the liver enzymes. In this sense, the protective role of NAMPT in non-alcoholic fatty liver disease (NAFLD) [52] and its involvement in portal inflammation in NAFLD patients has been recently reported [53]. NAD is a coenzyme with important roles in a variety of biological processes in part through the activation of sirtuin-1, a NAD(þ)-dependent histone deacetylase involved in the control of metabolic processes [54].…”
Section: Discussionmentioning
confidence: 99%
“…Serum visfatin level was higher in obese than non-obese patients, and it was lower in non-alcoholic steatohepatitis patients than in those with simple steatosis or obese controls (Jarrar et al, 2008). In addition, visfatin level was shown to predict the presence of portal inflammation in non-alcoholic fatty liver disease patients (Aller et al, 2009). Visfatin was preferentially www.intechopen.com expressed by visceral adipose tissue compared with subcutaneous fat (Fukuhara et al, 2005).…”
Section: Visfatinmentioning
confidence: 99%